Impact of Exercise on Innate Immunity in Multiple Sclerosis Progression and Symptomatology - Barry, Alison; Cronin, Owen; Ryan, Aisling M.; Sweeney, Brian; Yap, Siew M.; O'Toole, Orna; Allen, Andrew P.; Clarke, Gerard; O'Halloran, Ken D.; Downer, Eric J. (Frontiers in Physiology, 2016)
Multiple Sclerosis (MS), an idiopathic progressive immune-mediated neurological disorder of the central nervous system (CNS), is characterised by recurrent episodes of inflammatory demyelination and consequent axonal deterioration. It accounts for functional deterioration and lasting disability among young adults. A body of literature demonstrates that physical activity counteracts fatigue and depression and may improve overall quality of life in MS patients. Furthermore, much data indicates that exercise ameliorates chronic neuroinflammation and its related pathologies by tipping cytokine profiles towards an anti-inflammatory signature. Recent data has focused on the direct impact of exercise training on the innate immune system by targeting toll-like receptors (TLRs), signalling pattern recognition receptors that govern the innate immune response, shedding light on the physiological role of TLRs in health and disease. Indeed, TLRs continue to emerge as players in the neuroinflammatory processes underpinning MS. This review will highlight evidence that physical activity and exercise are potential immunomodulatory therapies, targeting innate signalling mechanism(s) to modulate MS symptom development and progression.